A review on the utilization of municipal solid waste incineration (MSWI) bottom ash as a mineral resource for construction materials - Chen, Boyu; Perumal, Priyadharshini; Illikainen, Mirja; Ye, Guang (Journal of Building Engineering, 2023)
In recent years, the widespread application of waste incineration technology has led to an increased generation of municipal solid waste incineration (MSWI) bottom ash. There is growing interest in the use of MSWI bottom ash as a mineral resource to produce construction materials. The utilization potential of MSWI bottom ash is determined by its chemical and mineralogical compositions, which can vary from incineration plant to incineration plant, and even from batch to batch within a single incineration plant. The quality of MSWI bottom ash often needs to be improved before it can be used as supplementary cementitious material (SCM) and precursor for alkali-activated materials (AAM). This review summarizes the composition of MSWI bottom ash sourced from different regions and the proposed treatments for quality upgrades of MSWI bottom ash. The reactivity of MSWI bottom ash as SCM and AAM precursor is discussed. Finally, the challenges regarding the use of MSWI bottom ash as a mineral resource for the production of construction materials are examined and possible solutions are provided. [Display omitted] •Characteristics of MSWI bottom ash sourced from different regions are summarized.•Effect of pre-treatments on the chemical properties of MSWI bottom ash is analyzed.•Suggestions are made for the use of MSWI bottom ash as SCM and AAM precursor.